HUBUNGAN SEXTAN YANG MENGALAMI GINGIVITIS DENGAN USIA KEHAMILAN PADA IBU HAMIL DI PUSKESMAS MANGGIS II KABUPATEN KARANGASEM TAHUN 2019 - Asep Arifin Senjaya; Ni Wayan Arini; Ni Ketut Ratmini; Ni K. Ayu Suri S. Handayani (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
It is very important for pregnant women to maintain healthy teeth and mouth during pregnancy. It is even expected for expectant mothers before planning a pregnancy, paying attention to the state of their oral health. During pregnancy, acid levels in the mouth increase due to nausea and vomiting which are usually experienced by pregnant women. In addition, pregnant women are also prone to gum inflammation that is compounded by the hormones progesterone and estrogen. Gingivitis in pregnant women increases with gestational age. Handayani's research concluded that all pregnant women in the Manggis II Health Center had gingivitis. The purpose of this study was to determine the relationship between sextans who had gingivitis and gestational age among pregnant women at the Manggis II Health Center in Karangasem Regency in 2019. Cross sectional research method. Using secondary data, with 45 respondents. Spearmen correlation test results sig 0.013. Conclusion: there is a relationship between sextans who have gingivitis and gestational age in pregnant women at Manggis II Health Center in Karangasem Regency in 2019.